Max Aub, 'La censura' y lo mexicano de los "Cuentos mexicanos" - Núñez, César Andrés (El Colegio de México, 2012)
This work analyzes the representation of Mexico things in the shortstory “Censorship” by Max Aub, which was published in the 1959collection Mexican stories (with a small gift). Although this book waslargely read in light of the realist aesthetic, some of the stories cannotproperly be classified as realist narratives. “The branch”, “Censorship”,and “The Great War” do not seem to speak of the Mexico that thevolume’s title advertises. We therefore encounter the problematic caseof “Mexican” stories that do not refer to Mexico. This study considersthis phenomenon and proposes that the appearance of the space ofexile is intimately linked to a change in the author’s aesthetic. MaxAub abandons the realism to which he had strictly adhered when hewent into exile in the 1940s, and instead, he recovers methods thatare characteristic of the historical avant-garde to which he had belonged.In particular, the short story “Censorship” allows us to analyze asystem of veiled references; this system eschews direct reference butnonetheless uses literary allusion to point to a determined geographical,political, and social space.